Perbandingan Hasil Pemeriksaan Jumlah Eritrosit Menggunakan Antikoagulan K2edta dan K3edta Dengan Variasi Waktu Penundaan - Andraini, Okvi; Anggraeni, Rosmita; Suryanto, Suryanto (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Erythrocyte count examination is a crucial component of hematological analysis and plays a significant role in the clinical diagnostic process. One of the key factors affecting result accuracy is the type of anticoagulant used, as well as the delay time before examination. This study aims to compare erythrocyte count results using K2EDTA and K3EDTA anticoagulants with three delay time variations: immediately, after 1 hour, and after 2 hours. The study was conducted at Bumiayu Hospital using a comparative quantitative design with a cross-sectional approach. Venous blood samples from six patients were analyzed using a hematology analyzer, with six repetitions for each treatment combination. Normality was tested using the Shapiro-Wilk method, followed by a paired t-test to determine any significant differences. The results showed no statistically significant difference in erythrocyte counts between K2EDTA and K3EDTA at all delay times (p > 0.05). The sample size was determined using the Federer formula; however, statistically, this number was insufficient to detect small differences significantly. Therefore, the findings should be interpreted with caution, and future studies with larger sample sizes are recommended. Descriptively, K2EDTA tended to yield more stable and slightly higher erythrocyte values compared to K3EDTA, suggesting it may be more suitable for hematological examinations involving delayed analysis.